DRUG-COATED BALLOONS FOR THE TREATMENT OF STENT EDGE RESTENOSIS - JAN, MW; IKRAMULLAH, S; MAGSI, M; HADEE, A; KHAN, N; SAFDAR, T (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the effectiveness of Drug-Coated Balloon (DCB) treatment with New-Generation Drug-Eluting Stent (DES) implantation for Stent Edge Restenosis (SER). The study was conducted at LRH Peshawar from 11-02-2022 to 11-02-2023 and included 130 patients with stent edge restenosis. Ethical approval was obtained from the hospital's ethical committee, and informed consent was taken from all patients. Patients were divided into two groups, Group A (DES) and Group B (DCB), and their clinical outcomes were analyzed using propensity score matching (PSM). The study showed that DCB therapy reduced the risk of target lesion revascularization (TLR) compared to DES during a median follow-up period of 1080 days. After conducting PSM, there was no significant difference in the risk of TLR between the two groups. Moreover, there were no significant differences in the risk of all-cause death, major adverse cardiovascular events (MACE), or TLR between Group A and Group B. In conclusion, DCB treatment for SER was found to be equally as effective as new-generation DES following PSM. Therefore, DCB can be considered a viable alternative to the new-generation DES for treating SER.